Reliability Compliant Distribution System Planning Using Monte Carlo Simulation. Issue 11 (21st July 2019) - Battu, Neelakanteshwar Rao; Abhyankar, Abhijit R.; Senroy, Nilanjan
Abstract: Distribution system planning is imperative to meet the load growth and to enhance reliability of the system. Power supply interruption causes inconvenience to the customer. Some customers may even lose the opportunity cost due to unreliable power supply. This enforces to consider reliability aspects during distribution system planning. This paper proposes reliability compliant distribution system planning using genetic algorithm embedded Monte Carlo simulation. The proposed approach is applied to 15-bus and 33-bus radial distribution systems to find the optimal location and size of DG, and distribution system upgradation needed to meet the load growth and to enhance reliability of the system.